Benefit of part-time work for fulltime student of UiTM Sarawak / Nursabrina Mohd Sabri, Nur Nabilla Khairunnisa & Nuraimi Rasyidah Suwarno - Mohd Sabri, Nursabrina; Abdullah, Nur Nabilla Khairunnisa; Suwarno, Nuraimi Rasyidah (2011)
The purpose of the study us to analysis benefit of part time job for full time student and to seek out the most appropriate suggestions and recommendations in order to improve the performance of student who doing part time job in their studies and job. The level of respondent’s perception, experience and expectation were measured to identify whether part time job gives more advantages than disadvantages. Throughout the period of study, one hundred and forty-five (145) responses had been received and the data collected was analyzed. According to Smith, 2010 put it; “a part fime job is a job in which an employee does not work full hours. A part time job often has the advantage of more flexible hours. Sometimes employees can at least partially dictate their own schedules, thereby setting up a job which is in alignment with life and other needs.